On the Application of the Variational Iteration Method to Klein-Gordon Equations - Gholizadeh Siahmazgi, Shohreh (Wake Forest University, 2023)
The variational iteration method (VIM), a well-known method in the field of numerical analysis of partial differential equations, is formulated in a rigorous way that is suitable for the analysis of the solutions of Klein-Gordon equations. Usingthis formulation, it is shown the sequence of the approximate solutions constructed by the VIM converges to the exact solution in the two cases of the Klein-Gordon problems: